Choroby duszy i ciała człowieka według brytyjskich i irlandzkich ksiąg pokutnych - Witowski, Wojciech Marek (Vox Patrum, 2021)
The reality of illness is inscribed in human life. It affects both the human body, in the form of various ailments and indispositions, and, through sin, it touches his soul in an analogous way. Since human being consists unity, he must take care of both the body and the soul, without neglecting any element that makes up his humanity. In this article, the author answers the question of how the illness of the soul and body of man were understood in the Christian antiquity in the Irish Church. To achieve this goal, he analyzed selected canons from Irish and British penitential books. Penitencials mainly concern the religious life of the people of that time, therefore the analysis revealed more information about the spiritual illness, that is sin and the medications for its treatment. As far as the source material allowed, the analysis also took into account the physical aspect of the disease. The method used allowed to draw a picture of the disease of the human soul and body in late antiquity, based on Irish and British penitential books.